Efficacy of Extraction Methods of Moringa oleifera Leaf Extract for Enhanced Growth and Yield of Wheat - Muhammad Umer Chattha; Imran Khan; Muhammad Umair Hassan; Muhammad Bilal Chattha; Muhammad Nawaz; Asif Iqbal; Nazar Hussain Khan; Naveed Akhtar; Muhammad Usman; Mina Kharal; Muhammad Aman Ullah (Journal of Basic & Applied Sciences, 2018)
A field study was conducted to assess effective method to get Moringa leaf extract, through its response on growth and yield traits of wheat. Extracts of whole or chopped and dry or fresh Moringa leaves were used exogenously i.e. pre-sowing seed soaking as well as water diluted solution based foliar spray application at tillering and booting stages. Significantly higher growth response in term of leaf area index, leaf area duration, and crop growth rate was observed when combination of 30 times diluted moringa leaf extract (MLE) was applied at both crop stages. Yield contributing traits of wheat such as fertile tillers, spikelet’s spikelet’s per spike, grains per spike, 1000 grain weight, biological and grain yields were recorded in significantly higher due to 30 times diluted fresh MLE followed by 20 times dilution of Moringa dried leaf powder (DLP). While, control treatment and hydro-priming showed at comparable results in the form of significantly lesser fertile tillers, grains per spike, 1000-grain weight and grain or biological yields. Conclusively, 30 times diluted MLE proved the best among the treatments combinations for improved wheat growth and yield however, the biochemical features responsible for such promotive response are yet to be investigated prior to dissemination of this technology to the farmer field.